2012
DOI: 10.1002/ps.3418
|View full text |Cite
|
Sign up to set email alerts
|

Role of sterol 3‐ketoreductase sensitivity in susceptibility to the fungicide fenhexamid in Botrytis cinerea and other phytopathogenic fungi

Abstract: erg27 mutation and erg27 polymorphism may therefore contribute to the unfavourable binding of fenhexamid to its target, 3-ketoreductase, explaining the acquisition of fenhexamid resistance in B. cinerea and the narrow spectrum of this fungicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
0
16
0
1
Order By: Relevance
“…The occurrence of fenhexamid resistance with a frequency of 0-37.5% among nine locations in Zhejiang Province suggests that there exists natural resistance towards fenhexamid in B. cinerea. More recently, Debieu et al 44 reported that erg27 mutations in B. cinerea fenhexamid-resistant strains and erg27 genetic polymorphism in fenhexamid-resistant fungal species may contribute to the unfavourable binding of fenhexamid to its target, 3-ketoreductase, which is supported by our sequence analysis of the erg27 gene from the 74 HydR isolates. In this study, seven new mutations S9G, P57A, P269L, V365A, E368D, E375K and A378T were detected for the first time within 73 HydR isolates from Zhejiang Province.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The occurrence of fenhexamid resistance with a frequency of 0-37.5% among nine locations in Zhejiang Province suggests that there exists natural resistance towards fenhexamid in B. cinerea. More recently, Debieu et al 44 reported that erg27 mutations in B. cinerea fenhexamid-resistant strains and erg27 genetic polymorphism in fenhexamid-resistant fungal species may contribute to the unfavourable binding of fenhexamid to its target, 3-ketoreductase, which is supported by our sequence analysis of the erg27 gene from the 74 HydR isolates. In this study, seven new mutations S9G, P57A, P269L, V365A, E368D, E375K and A378T were detected for the first time within 73 HydR isolates from Zhejiang Province.…”
Section: Discussionmentioning
confidence: 58%
“…The codons V365, E368, E375 and A378, as well as codon N369, are near to the C-terminal putative transmembrane domain of erg27 which was found to play a role in 3-ketoreductase activity. 44,45 The amino acid leucine at position 269 is also present in the erg27 protein in B. pseudocinerea, which carries 12 amino acid residues different from those of the sensitive B. cinerea strain. 15 Amino acids P57 and S9 are located in domains of still unknown function.…”
Section: Discussionmentioning
confidence: 98%
“…It is known that B. cinerea can rapidly adapt to the environment and develop resistance, but it is susceptible to photosensitization (Luksiene, 2005;Luksiene, Paskeviciute, 2011). Benzimidazoles fungicides were introduced for plant disease control in the 1960's, but within a few years resistance emerged (Kretschmer, Hahn, 2008;Debieu et al, 2013;Rodríguez et al, 2014). Our research was carried out to test the new nonchemical measures reducing B. cinerea on berry fruits.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the highly resistant HydR3 + isolates were found to contain point mutations leading to amino acid changes at position F412S, F412I or F412V, while similar studies have shown that other changes at L195F, S336C, V309M, A314V, N369C and L400S/F can also lead to fenhexamid resistance (Billard et al., ; Fillinger et al., ; Weber, ). Another study of fenhexamid‐resistant (HydR) isolates in Zhejiang identified seven amino acid changes (S9G, P57A, P269L, V365A, E368D, E375K and A378T) that could be important in fenhexamid resistance (Yin et al., ), and it has been suggested that these mutations and genetic polymorphism in the erg27 genes of fenhexamid‐resistant isolates of B. cinerea could contribute to the unfavourable binding of fenhexamid to its 3‐ketoreductase target (Debieu et al., ; Yin et al., ). The molecular analysis of the resistant isolates (163‐6 and 163‐22) collected from Xinjiang in the current study indicated that they contained three of the four mutations, V365A, E368D and A378T, associated with the type II resistant mutant TZ2‐5 characterized by Yin et al.…”
Section: Discussionmentioning
confidence: 99%
“…Fenhexamid is known to inhibit the 3‐ketoreductase enzyme ( erg27 ), which is part of the ergosterol biosynthesis pathway of B. cinerea , and specific amino acid mutations in this protein have been associated with resistance to fenhexamid (Grabke, Fernández‐Ortuńo, & Schnabel, ). It has been suggested that these mutations and genetic polymorphism of the erg27 gene can reduce the binding affinity of fenhexamid to its 3‐ketoreductase target (Debieu, Bach, & Montesinos, ; Yin, Wu, Liu, Yin, & Ma, ). Although fenhexamid has not yet been registered for use on any crops in China, a recent report detailed the occurrence of fenhexamid‐resistant isolates of B. cinerea in strawberry crops grown in Zhejiang Province (http://www.chinapesticide.gov.cn/; Yin et al., ).…”
Section: Introductionmentioning
confidence: 99%